A new species and new records of Pachychernes Beier, 1932 from Colombia (Pseudoscorpiones, Chernetidae) - Marimon, Karla; Villarreal-Blanco, Eduardo; Romero-Ortiz, Catalina; Gutierrez, Luis C. (Zootaxa, 2021)
In Colombia, the status of the Neotropical genus Pachychernes Beier, 1932 is unknown. The only available data in literature to support the presence of this genus is an adult of P. aff. subrobustus, possibly female, from copal resin without specific locality data, and a record at generic level from Northern Colombia. In this study, we extend the distribution of Pachychernes by describing a new species, P. florezi sp. n. and several reporting individuals of P. zehorum Muchmore, 1997 from Montes de María and the Caribbean coast of the country. These species are clearly differentiated from one another by the sexual dimorphism in the latter species, with a depression on the tarsus I in males. We also present an updated key for all species of the genus.